PHYTOCHEMICAL AND ANTIMICROBIAL SCREENING AND NUTRITIONAL QUALITIES OF FICUS SUR (FORSSK) - Ojukwu U.P; ibekwe, O. F (International Journal of Engineering Technologies and Management Research, 2018)
The preliminary study of the leaf of Ficus Sur (Forssk) was conducted to ascertain its medicinal and nutritional qualities. Phytochemical analysis and antimicrobial activity were conducted. Micro elements and vitamins B and C were also determined by atomic absorption spectrophotometry and titrimetry respectively. Results of the analysis revealed the presence of iron, copper, magnesium and manganese as well as vitamin C and B at various levels. The leaf was found to show antimicrobial activity against many bacteria such as Enterobacter aerogens, Bacillus species, Pseudomonas pyocyania and Staphylococcus aureus. Antifungal activity against Aspergillus niger and Aspergillus flavus was also established. The phytochemical study indicated the presence of flavonoids, saponins, alkaloids, tannins, proteins, reducing sugar, fats and oil and carbohydrate. The leaf extract of this plant can therefore satisfactorily cure diseases like anemia, malnutrition, cold and supportive infections like boil, skin pustules, conjunctivitis, septicaemia, intestinal diseases, food poisoning, surgical wounds and burns, acute bacterial endocarditis and bacterimia.